Одесский археологический музей и государственные структуры власти (Российская империя, СССР, Украина) - Охотников, С.Б. (Материалы по археологии Северного Причерноморья, 2011)
Odessa Archaeological Museum was blessed by high attention of state authorities from the very beginning of its existence (1825). Its foundation was patronized by General-Governor M.S.Voronzov as far as foundation and activities of Odessa Society of History and Antiquities. The Society was granted by a denomination "Emperor's" by tsar Alexander II. During Soviet times, museum was a part of Ministry of culture system and in 1971 it was transferred to Academy of Sciences of URSR. After Ukraine gained its independence, several Orders of state authorities mentioned the Museum: the Order pf President on the organization of Museum's branch on Zmeiny island and the Order by Cabinet of Ministers on the inclusion of Museum's collections in the list of National Heritage.